The role of extracellular vesicles in renal fibrosis - Jing, H. (Cell Death Dis, 2019)
As a particularly important mediator of intercellular communication, extracellular vesicles (EVs) have been proved to be extensively involved in various system diseases over the past two decades, including in renal diseases. As is well-known, renal fibrosis is the common pathological process of any ongoing renal disease or adaptive repair of kidney injury based on current knowledge. Although much work has been performed focusing on EVs in various renal diseases, the role of EVs in renal fibrosis has not been described in detail and summarized. In this review, we provide a brief overview of the definition, classification and biological process of EVs. Then, the potential mechanisms of EVs in renal fibrosis are illustrated. Lastly, recent advances in EVs and the implications of EVs for diagnosis and therapy in renal fibrosis disease are introduced. We look forward to a more comprehensive understanding of EVs in renal fibrosis, which could be a boon to patients with renal fibrosis disease.